Extraction of Volatile Oil of Nigella sativa L. Using Multivariate Analysis - Khatoon, B.A. (Asian Journal of Chemistry, 2011)
The present study investigate multivariate analysis to extract volatile oil of Nigella sativa L. cultivated in Middle East and East of Asia. Each cultivated seed used to extract volatile oil by specific method. The used method affect both the quantity and compound of the oil. To determine the best method factor analysis was applied and out of five different methods, three methods are recommended.